The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12889-022-14790-6
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy food and beverage marketing to children on digital platforms in Aotearoa, New Zealand

Abstract: Background Children’s exposure to unhealthy food and beverage marketing has a direct impact on their dietary preference for, and consumption of, unhealthy food and drinks. Most children spend time online, yet marketing restrictions for this medium have had slow uptake globally. A voluntary Children’s and Young People’s Advertising (CYPA) Code was implemented in Aotearoa, New Zealand (NZ) in 2017. This study explores the Code’s limitations in protecting children from harmful food and beverage ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Adolescents in Savona et al's work also identified the influence of large food manufacturers and advertisers as an strong driver of the consumption of unhealthy food [15]. Of particular concern is the concentration of advertising around commercial sites of sale [43], the concentration of fast-food outlets in low advantage communities [44], particularly schools [45,46], and the two-fold exposure of Māori children to unhealthy food and drink marketing compared to non-Māori children [47].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents in Savona et al's work also identified the influence of large food manufacturers and advertisers as an strong driver of the consumption of unhealthy food [15]. Of particular concern is the concentration of advertising around commercial sites of sale [43], the concentration of fast-food outlets in low advantage communities [44], particularly schools [45,46], and the two-fold exposure of Māori children to unhealthy food and drink marketing compared to non-Māori children [47].…”
Section: Discussionmentioning
confidence: 99%
“…There is robust evidence that traditional forms of marketing increase consumption of harmful products (Babor, 2010;Babor et al, 2022;Garde et al, 2018;Sing et al, 2022). But because of the nature of digital and social media marketing, this effect is exacerbated (Buchanan et al, 2018;Montgomery and Chester, 2009;Tatlow-Golden and Garde, 2020;VicHealth, 2020;World Health Organization, 2022, 2023; World Health Organization Regional Office for Europe, 2016Europe, , 2021.…”
Section: Digital Marketing Of Harmful Commodities: Insidious Opaque A...mentioning
confidence: 99%
“…According to a 2022 study, 85% of posts and videos on company Facebook pages and YouTube channels for the most popular packaged food, fast food and non-alcoholic beverage brands/companies in New Zealand featured unhealthy food or drinks (Garton, Gerritsen et al, 2022). The AdHealth study (Kidd et al, 2021) assessed the exposure of New Zealand Facebook users aged 16-18 to 'paid' food advertisements.…”
Section: Unhealthy Foodmentioning
confidence: 99%
“…Existing nutrition policy has failed Māori ( Theodore et al , 2015 ). Furthermore, a lack of government regulation in relation to food marketing has failed to adequately protect Māori children, and therefore could be considered a breach of the Te Tiriti ( Theodore et al , 2015 ; Garton et al , 2022 ). Changes to the food environment, through the expansion of the digital environment will be considered in line with responsibilities under Te Tiriti from a health equity perspective,…”
Section: Introductionmentioning
confidence: 99%